Sub-Saharan Africa and the resource curse: Limitations of the conventional wisdom - Sam Jones (Danish Institute for International Studies (DIIS), 2008)
The existence of a natural resources curse is widely accepted in academic and policy circles. With its focus on institutional quality, the resource curse thesis is symptomatic of the current 'good governance' agenda. This paper subjects the thesis to critical evaluation and finds it wanting. It is argued that empirical evidence is ad hoc and theoretical explanations remain weakly developed. The need for more nuanced approaches is confirmed by exploratory empirical techniques. The thesis does not provide a robust basis for practical interventions. Rather, acknowledgement of our ignorance is a first step towards widening policy space and promoting local solutions.
Keywords: 330; Natürliche Ressourcen; Entwicklung; Public Choice; Kritik; Afrika südlich der Sahara